HUBUNGAN KOMUNIKASI INTERPERSONAL DAN PEMAAFAN DENGAN KEBAHAGIAAN SUAMI ISTRI - Nurhayati Nurhayati (LP3M IAI Al-Qolam, 2017)
The objective of this study is to examine whether or not there is a correlation between interpersonal communication and forgiveness and spouses happiness. The subject of this study was 200 spouses in Malang regency. Interpersonal Communication Inventory (ICI) was used to measure interpersonal communication, Transgression-Related Interpersonal Motivation (TRIM) was used to measure forgiveness, and Oxford Happiness Inventory (OHI) was used to measure happiness. The result of the data analysis using multiple regression tests was that there is a positive and significant correlation between interpersonal communication and happiness, between forgiveness and happiness, between interpersonal communication and forgiveness and spouses happiness (R= .729, P= 0.000) Keywords: interpersonal communication, forgiveness, spouses happiness